2009
DOI: 10.1002/pd.2323
|View full text |Cite
|
Sign up to set email alerts
|

Does the combination of fronto‐maxillary facial angle and nasal bone evaluation improve the detection of Down syndrome in the second trimester?

Abstract: While FMF angle and NB are independent markers for DS, their combination resulted in a minimal but nonsignificant improvement in DS detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…The present study of a Thai population demonstrated that FMF angle does not vary with gestational age, which is in agreement with the study by Molina et al [5]; however, some studies have given conflicting results [6,11].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study of a Thai population demonstrated that FMF angle does not vary with gestational age, which is in agreement with the study by Molina et al [5]; however, some studies have given conflicting results [6,11].…”
Section: Discussionsupporting
confidence: 82%
“…Odibo et al [11] found that the combination of FMF angle and nasal bone hypoplasia did not increase the detection rate, but the present study demonstrated a significant increase in detection rate. Ethnic differences may play a significant role, and the different cut-offs for abnormal FMF angle and nasal bone hypoplasia used in the present study might also contribute to the different finding.…”
Section: Discussioncontrasting
confidence: 35%
“…FMF angle measurement in normal second‐trimester fetuses has previously been performed by Sonek et al 5 and Odibo et al 14 using 2D ultrasound and by Molina et al 7 using 3D ultrasound. Consistent with the findings of Molina et al and in contrast to those of Sonek et al and Odibo et al , our results show a constant FMF angle measured from the palate and a slight increase in the FMF angle measured from the vomer through gestation (Figure 4), although the latter was not statistically significant, possibly due to the small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…. The results of other single markers, such as the frontomaxillary facial angle, were promising but not good enough for use in routine screening for trisomy 21.…”
Section: Discussionmentioning
confidence: 96%